2015
DOI: 10.1073/pnas.1418155112
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and aggregation of intrinsically disordered peptides

Abstract: Intrinsically disordered proteins (IDPs) are a unique class of proteins that have no stable native structure, a feature that allows them to adopt a wide variety of extended and compact conformations that facilitate a large number of vital physiological functions. One of the most well-known IDPs is the microtubule-associated tau protein, which regulates microtubule growth in the nervous system. However, dysfunctions in tau can lead to tau oligomerization, fibril formation, and neurodegenerative disease, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
207
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(217 citation statements)
references
References 37 publications
10
207
0
Order By: Relevance
“…Consistently, a recent study of ( 273 GKVQIINKKLDL 284 ) peptide has shown that the balance between hydrogen bonds and salt bridge formation in IDPs can dramatically shift IDPs from compact ensembles to extended ones. 37 The observed behavior could be the first step of Aβ cross-seeding tau into prion-like aggregation. Contrary to common intuition that Aβ's cross-seeding of tau will enhance tau's beta structure content, it is more likely that Aβ first stretches tau into more open states permitting intermolecular stacking that will finally aggregate into fibril.…”
Section: Lettermentioning
confidence: 96%
“…Consistently, a recent study of ( 273 GKVQIINKKLDL 284 ) peptide has shown that the balance between hydrogen bonds and salt bridge formation in IDPs can dramatically shift IDPs from compact ensembles to extended ones. 37 The observed behavior could be the first step of Aβ cross-seeding tau into prion-like aggregation. Contrary to common intuition that Aβ's cross-seeding of tau will enhance tau's beta structure content, it is more likely that Aβ first stretches tau into more open states permitting intermolecular stacking that will finally aggregate into fibril.…”
Section: Lettermentioning
confidence: 96%
“…Such proteins can form compact regular structures only during interactions with their partners [102]. A number of studies have indicated the possibility that native disordered proteins can assume a compact regular structure in osmolyte solutions without interacting with their corresponding partners [66,[103][104][105][106]. As an example, a study on RNAse P [66] uncovered the fact that the native protein structure in a complex with RNA and the structure that emerges during renaturation of this protein in TMAO solution are similar but not identical, while the paths by which this protein folds in the presence of RNA and it is absence, but in the presence of TMAO, are considerably different.…”
Section: Osmolytes and Native Internally-disordered Proteins; Osmolytesmentioning
confidence: 99%
“…1A, Left). Although Tau strongly binds to the MT surface (∼1-3 μM affinity) (10,26), recent work suggests that Tau-MT interactions are highly dynamic and that Tau can assume numerous structures (30,31).…”
Section: Significancementioning
confidence: 99%